2004
DOI: 10.3171/jns.2004.100.3.0376
|View full text |Cite
|
Sign up to set email alerts
|

Successful use of the new high-dose mannitol treatment in patients with Glasgow Coma Scale scores of 3 and bilateral abnormal pupillary widening: a randomized trial

Abstract: Ultra-early high-dose mannitol administration in the emergency room is the first known treatment strategy significantly to reverse recent clinical signs of impending brain death, and also to contribute directly to improved long-term clinical outcomes for these patients who have previously been considered unsalvageable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(48 citation statements)
references
References 41 publications
0
45
0
3
Order By: Relevance
“…Among the various osmotic agents available for administration to treat cerebral edema, mannitol (administered rapidly in a 1 gm/kg bolus) has been the most commonly selected medication in the neurointensive care setting [21]. However, mannitol may lead to systemic hypotension, decreased cerebral perfusion, acute renal failure, and Conducts monovalent cations Absorption of free water in collecting tubule of kidney delayed accumulation within the extravascular compartment that leads to a paradoxical rebound elevation in intracranial pressure [22,23].…”
Section: Osmotherapymentioning
confidence: 99%
“…Among the various osmotic agents available for administration to treat cerebral edema, mannitol (administered rapidly in a 1 gm/kg bolus) has been the most commonly selected medication in the neurointensive care setting [21]. However, mannitol may lead to systemic hypotension, decreased cerebral perfusion, acute renal failure, and Conducts monovalent cations Absorption of free water in collecting tubule of kidney delayed accumulation within the extravascular compartment that leads to a paradoxical rebound elevation in intracranial pressure [22,23].…”
Section: Osmotherapymentioning
confidence: 99%
“…They explained their results as related with young age, initially aggressive treatment and the epidural hematoma (EDH) subgroup, and they emphasized that patients who suffered TBI and presented with a GCS score of 3 should be treated aggressively initially, since a good functional outcome could be obtained in some cases. Cruz et al [8] reported that among patients with SHI and BNDP who were treated with ultra-early high-dose mannitol, 43.5% had a favorable outcome at six months. They also reported that patients with abnormal pupillary widening documented at the scene of the injury did not benefit from ultra-early high-dose mannitol treatment, in contrast to those whose bilateral widened pupils were first seen in the ER.…”
Section: Gcs Score Icp and Cpp Changes And Prognosismentioning
confidence: 99%
“…[6] When the patient demonstrates compression signs of the upper brainstem in the early period of uncal or central transtentorial herniation due to uncontrollable ICP, despite the modern management protocols (intubation, artificial ventilation, ventricular drainage of cerebrospinal fluid (CSF), and osmotherapy with mannitol), DC has been recommended as a last treatment option. [7][8][9][10][11] However, the criteria for the use of DC in such patients with severe traumatic brain injury (STBI) have not been standardized. There are not many reports in the current literature about the necessity of decompressive surgery (DS) in patients with BNDP due to STBI or cerebrovascular accidents (CVA).…”
mentioning
confidence: 99%
“…En cuanto a la dosis y la forma de administración, los distintos estudios encuentran que es efectivo a dosis de 0,25-1 g/kg peso, pero no hay resultados concluyentes sobre su uso en bolo o en infusión continua, aunque ésta parece que conlleva mayor incidencia de rebote 23,24 . Los estudios de Cruz et al 25,26 sobre la efectividad de altas dosis (1,4 g/kg) en pacientes con lesiones focales y con alteraciones pupilares han sido cuestionados por su metodología.…”
Section: Soluciones Osmolaresunclassified